A diagnosis for updating the study plan of the Bachelor of Arts in Modern Languages, specialization in French and English, Department of Foreign Languages, University of El Salvador, year 2020 - Alfaro Escamilla, Madelyn Elizabeth; Dubón Aguilar, Flor Maritza; Menjivar Escobar, Jocelyn Yajaira (2024)
This research diagnoses opinions of three sectors (professors, students and graduates) on a needed curricular update of the Modern Languages major through an exploratory study of the current academic plan, and it is grounded on curriculum design theories and models. Towards that end, surveys and interviews, as part of a mixed research approach, will be used to gather and, afterwards, analyze data which will unveil results leading to potential curricular changes. In short, expected latest and freshest research results might well serve the purpose of a curricular update which is undoubtedly needed after 18 years of this study plan approval (Modern Languages study plan was approved in 2002)